Pedagogical interaction as a basis for quality training of future preschool education teachers - Prytuliak, L. (Problems of Engineer-Pedagogical Education, 2020)
The essence of the definitions of «interaction», «pedagogical interaction», and «pedagogical communication» is considered in the article. Particular attention is paid to the conditions of effective organization of pedagogical interaction between the university teacher and future preschool teachers. Based on the study of scientific sources on this issue, primary approaches to the interpretation of the essence of these definitions are analyzed and their content is revealed. It is determined that the main task of the institution of higher pedagogical education is to develop the personality of the future preschool teacher. Higher education teachers significantly influence vocational training of future pedagogues at all stages of their education. While carrying out educational activities, professors should demonstrate a general culture of behavior, in particular communicative and interactive, to students who will then realize their communicative culture in their own professional activities when communicating with the subjects of the educational process of the institution of preschool education. It is stated that it is the university teacher who must understand the consequences of improper organization of pedagogical communication and the complexity of solving communication problems. It has been found out that the key component of quality training of future preschool educators is pedagogical interaction, which is interpreted as interaction that provides not only the integrity necessary for the full implementation of the system of vocational training of future preschool educators, but also creates conditions for their further professional development and optimal adaptation to a dynamic educational environment. It is emphasized that pedagogical interaction should not be authoritarian but should be based on the principle of cooperation and partnership in the relationship between the teacher and students, which consists in their joint developmental activity, characterized by mutual understanding, collective analysis of the course and results of these activities. Pedagogical interaction opens opportunities for self-realization of the individual and his or her self-organization in future professional activity. It is determined that relationships between the teacher and students are best revealed and implemented in pedagogical communication, which is interpreted as a set of methods and means that ensure the realization of the goals and tasks of formal training of future preschool teachers and determine the nature of interaction between the teacher and students.